The GABAA receptor agonist THIP alters the EEG in waking and sleep of mice. - Vyazovskiy, V; Kopp, C; Bösch, G; Tobler, I (2005)
THIP is a GABA(A) agonist with hypnotic properties consisting in reducing sleep latency and prolonging and consolidating sleep. THIP has been reported to increase EEG slow-wave activity (SWA; EEG power in the 0.75-4 Hz band) in non-REM (NREM) sleep in both rats and humans. We investigated the effects of THIP on sleep in C57BL/6 mice. EEG recordings were performed after 2, 4 and 6 mg/kg THIP and saline control. The results were compared with analyses of recordings obtained after 6 h of sleep deprivation (SD) in the same strain of mice. The two higher doses of THIP induced an abnormal EEG pattern both in waking and NREM sleep. The EEG was characterized by sporadic asymmetric high-voltage potentials recurring at a low-frequency (<1 Hz) on the background of a low-amplitude EEG pattern. In contrast, after SD the typical regular synchronous high amplitude delta waves predominated. THIP at 4 and 6 mg/kg led to a prominent enhancement of spectral power in the low-frequency range of the waking and sleep EEG which was much higher than the increase attained after 6 h SD. This effect was particularly prominent in the waking EEG. In NREM sleep the increase of spectral power after THIP reflected the frequency of recurrence of the high-voltage potentials, and was restricted to a narrower frequency band than after SD. The EEG changes after 2mg/kg differed little from saline control. Sleep latency was not affected by the two lower doses of THIP, and was prolonged after 6 mg/kg. REM sleep was suppressed after the two higher doses. In contrast to previous results reported in other species, THIP did not have a hypnotic action in mice. The changes induced by THIP in the waking and sleep EEG differed from those caused by enhanced physiological sleep pressure encountered after SD. Considering the abnormal EEG pattern and the similarity of the spectral changes in the sleep and waking EEG, THIP does not seem to exert a specific effect on mechanisms involved in sleep regulation.